2013
DOI: 10.1371/journal.pone.0082687
|View full text |Cite|
|
Sign up to set email alerts
|

Short-Term Azithromycin Treatment Promotes Cornea Allograft Survival in the Rat

Abstract: BackgroundAny inflammatory response following corneal transplantation may induce rejection and irreversible graft failure. The purpose of this study is to analyze the anti-inflammatory effect of azithromycin (AZM) following experimental keratoplasty in rats.MethodsCorneal transplants were performed between Fisher-donor and Lewis-recipient rats. Recipients were postoperatively treated three times daily with AZM, miglyol, ofloxacin or dexamethasone eye drops. As an additional control, AZM was applied following s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…Antibiotics are used to prevent ocular infection after ocular trauma or surgery, 3,13-15 while steroids are used to prevent ocular inflammation and NV and to prevent immunological reactions such as graft rejection after corneal keratoplasty. [16][17][18][19] Among antibiotics, fluoroquinolone has been used worldwide perioperatively for several decades. 14,15 Recently, fourth generation fluoroquinolones have been developed and employed for their broad antibacterial activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibiotics are used to prevent ocular infection after ocular trauma or surgery, 3,13-15 while steroids are used to prevent ocular inflammation and NV and to prevent immunological reactions such as graft rejection after corneal keratoplasty. [16][17][18][19] Among antibiotics, fluoroquinolone has been used worldwide perioperatively for several decades. 14,15 Recently, fourth generation fluoroquinolones have been developed and employed for their broad antibacterial activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, azithromycin did not show any anti-angiogenic activity compared with control groups, even though it has activity sufficient to increase graft survival after corneal keratoplasty in rat and mouse models. 8,19 The purpose of using topical eyedrops after various ocular surgeries is to decrease infection, inflammation and angiogenesis. 18 Anti-angiogenesis and anti-LY may be important effects of topical agents such as topical steroid agents which are used perioperatively after ocular surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Lokal kann jedoch keines der bisher publizierten Medikamente die Effizienz von topischem Kortison erreichen [6]. Kortison allein [37,38]. Es wird bereits klinisch bei verschiedenen entzündlichen Oberflächenerkrankungen des Auges erprobt [39].…”
Section: Gemeinsamkeiten Zwischen Beteiligten Hornhautzentrenunclassified
“…The effects of azithromycin in other organ transplantations have been previously shown. Azithromycin therapy following keratoplasty yielded results similar to those achieved with topical dexamethasone, without the risk of adverse effects commonly associated with steroidal drugs and enhanced graft survival in rats [ 17 ]. A study found that azithromycin promoted the survival of high-risk corneal allografts, apparently without modulating the immune system [ 18 ].…”
Section: Introductionmentioning
confidence: 99%